Presidential elections’97: attitudes and intentions of the electorate - Ališauskienė, Rasa (Politologija, 1998)
This article is based on the public opinion surveys carried out by the Lithuania-British public opinion and market research company "Baltics Surveys" (Gallup member) in 1992, 1996, 1997, and 1998. Main issues discussed in the article are, as follows: the evaluation of social change in Lithuania, the level of satisfaction with how democracy is developing in the country, attitudes towards the market economy and economic situation in the country, most important issues for the country and family, mood of the population, interest in politics and level of political participation, voting intentions, and the level of satisfaction with the election results. Empirical studies carried out over the last 6 years enabled the author to draw the following conclusions: before Presidential elections ’97, Lithuanians were of positive opinion towards the general situation in the country. Their attitude on the point of the way democracy has been developing in Lithuania has undergone noticeable changes. Furthermore, the majority of Lithuanians continue to support the development of a market economy in Lithuania. Over the last six years, the top issues to be solved in Lithuania remain the low standard of living, the threat of unemployment, and crime. For a long time, low levels of living standards and unemployment were the most urgent problems for Lithuanian families. Dealing with these issues, Lithuanians feel anxiety, and their psychological mood remains far from optimistic. Such concentration on everyday life issues has an impact on the level of political interests and political participation. Therefore, the interest in politics has diminished significantly since 1992. Only one out of ten adults in Lithuania felt greatly interested in politics before the Presidential elections. The level of interest is much higher among people with higher education. However, the level of intentions to vote in the Presidential elections ’97 was high - one out of three eligible voters were going to vote. The study conducted after the elections enabled us to conclude that the overall level of satisfaction with the results of the elections was high - six out of ten voters were satisfied with these results, in spite of the candidate they were voting for. In general, younger people, urban dwellers, and males are more optimistic than the other social groups in Lithuania. They are more supportive of the creation of a market economy as well as of better opinion of the way the country is developing. However, younger people are less interested in politics than the middle-aged and the elderly. Ideological orientation (left-right) still has the major impact on the overall evaluation of social change and processes in the country.